Influence of beach attributes on recreationists’ beach preferences: Evidence from Mombasa, Kenya - Atsieno, Jesca Ketura; Ndubi, Edgar; Bitok, Kipkosgei (Goodwood Publishing, 2025)
Purpose: This study examines how beach attributes influence preferences among resident recreationists in Mombasa County, Kenya, and explores how recreationists' characteristics moderate these preferences. Methodology/approach: A survey of 77 frequent beachgoers (visiting ?3 times weekly) was conducted at four beaches using enumerator-administered questionnaires. Descriptive statistics profiled demographics, exploratory factor analysis assessed environmental attitudes, conjoint analysis evaluated beach profile preferences (cleanliness, safety, congestion), and binary logistic regression examined moderating effects of demographics and attitudes. Results/findings: Clean, litter-free, patrolled, and uncrowded beaches were strongly preferred. Heavy litter and the absence of patrols significantly detracted from appeal, while congestion moderately reduced preferences. Gender significantly moderated the influence of congestion, highlighting differing valuations between male and female recreationists. These findings underscore the need for targeted management strategies to enhance beach experiences. Conclusion: The study reveals that extreme levels of key beach attributes-cleanliness, patrolling frequency, and congestion-significantly influence recreationists' preferences. Limitations: The cross-sectional design limits insights into the evolution of preferences over time. Longitudinal studies are recommended to assess how environmental education, management changes, and societal norms influence preferences. Additionally, the context-specific findings suggest a need for comparative studies across diverse regions. Contribution: This study contributes empirical evidence on resident beach preferences, an often-overlooked segment in tourism research. By applying conjoint analysis, it provides nuanced insights into how varying levels of cleanliness, safety, and congestion shape preferences, offering actionable guidance for beach management and policy.